Presença de Leishmania sp em equinos de zona urbana de Uruguaiana, Rio Grande do Sul - Escobar, Taiane Acunha (2015)
Leishmaniasis is an parasitic infectious disease caused by protozoa genus Leishmania and transmitted by the sandfly vector. Characterized as Neglected Tropical Disease, affects several species of mammals, and the dog are main reservoir in urban areas. The horses can also be infected especially when they are in contact with reservoirs or vectors. In Uruguaiana’s city, there is a significant number of horses used in the tensile loads and means of transport, with constant movement within the city, living in precarious work’s conditions, subjected to excessive and poor nutrition. In view of these factors added to the current epidemiological situation of LVC in the city, the present study aim to identify the presence of Leishmania in urban horses the municipality of Uruguaiana-RS. For the experiment, blood samples from 192 horses were used for holding three techniques: serological (ELISA), immunochromatographic (TR-DPP) and molecular (PCR). For conducting ELISA’s Test serum was used and tested with Bio-Manguinhos kit and for TR-Dual Path Platform Rapid Test whole blood samples were employed. In the PCR technique, DNA was extracted from peripheral blood of animals and amplifications were performed with primers RV1 / RV2, LITSR / LITSV, LITSR / L5.8S / LITSV / L5.8SR.. All tested samples showed negative results in immunoassays. However, employing sensitive techniques such as PCR, positive samples were detected. Considering the four primer pairs tested, 75 animals were positive, 52 with at least one of the pairs. However, when analyzing the individual primers, 58.6% were positive for LITSV/L5.8SR, 44% to LITSV/LISTSR, 28% for RV1/RV2, and 4% LITSR/L5.8S.In The results presented in the experiment indicate the possibility of Leishmania in horses in the region of Uruguaiana city, although serological tests have not submitted reactivity to Leishmania. Molecular technich shows results to consider the Leishmania’s presence in horse’s peripheral blood samples. This was the first report of infection in equine species in westernmost region of the Rio Grande do Sul state. However, it is important to conduct sequencing of the fragment so that we can confirm the genetic identity of Leishmania sp.